2020
DOI: 10.1097/md.0000000000022893
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of myocardial injury after non-cardiac surgery in high-risk patients who underwent radical cystectomy

Abstract: Radical cystectomy is considered the standard treatment for patients with muscle-invasive bladder tumors and has high postoperative complication rates among urological surgeries. High-risk patients, defined as those ≥45 years of age with history of coronary artery disease, stroke, or peripheral artery disease or those ≥65 years of age, can have a higher incidence of cardiac complications. Therefore, we evaluated the incidence, risk factors, and outcomes of myocardial injury after non-cardiac surgery (MINS) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…5 In our study, the increased baseline troponin and pre and postoperative NT-proBNP levels in MINS patients reflected the impaired ventricular diastolic function associated with hypertension-induced ventricular hypertrophy and, in turn, with a reduced ability to adapt to acute volemic shifts and increased ventricular afterload. 2,20 In contrast with previous studies that focused on patient risk factors, for the first time, we identified procedure-related factors, namely prolonged surgery and need for transfusion, as important contributors to the development of MINS in the entire and matched cohorts. The higher postoperative weight gain and SIRS reflected the severity of surgery along with intense neuroendocrine and inflammatory responses to extensive tissue trauma.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…5 In our study, the increased baseline troponin and pre and postoperative NT-proBNP levels in MINS patients reflected the impaired ventricular diastolic function associated with hypertension-induced ventricular hypertrophy and, in turn, with a reduced ability to adapt to acute volemic shifts and increased ventricular afterload. 2,20 In contrast with previous studies that focused on patient risk factors, for the first time, we identified procedure-related factors, namely prolonged surgery and need for transfusion, as important contributors to the development of MINS in the entire and matched cohorts. The higher postoperative weight gain and SIRS reflected the severity of surgery along with intense neuroendocrine and inflammatory responses to extensive tissue trauma.…”
Section: Discussionmentioning
confidence: 83%
“…In agreement with previous studies, MINS was associated with increased 60-day mortality and a higher incidence of MACEs. 1,4,6,20,22,23 Criteria for postoperative MI were met in only 5 patients, whereas 104 others exhibited transient elevations in cTnI/ TnT without ECG abnormalities or clinical signs of myocardial ischemia. In contrast with the short-term negative impact of MINS on clinical outcome, survival up to 30 months after surgery was related mainly to the presence cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies included all types of non-cardiac surgery in their eligibility criteria 2 , 15 , 22 , 30 , 33–35 , 37 , 38 , 40 , 43 , 44 , 46–49 , 51 , 56 , 58 , 60–62 , 65 . Seventeen studies focused on specific surgical subspecialties including vascular 28 , 39 , 41 , 42 , 45 , 52–54 , orthopaedic 29 , 31 , 32 , 50 , 55 , 59 , 64 , urology 36 , 63 and thoracic surgery 36 , 63 . Regarding surgical acuity, only two studies focused on emergency non-cardiac surgery 31 , 32 , whilst nine studies specifically included only patients undergoing elective surgery 28 , 35–38 , 52 , 53 , 58 , 63 .…”
Section: Resultsmentioning
confidence: 99%
“…A study by Parker et al [ 31 ] stated that approximately 25% of patients undergoing RC with PBT experience an infection within 30 days of surgery. Further reports demonstrated that myocardial injury occurred in 14.1% of patients with incidence of PBL and PBT during RC [ 32 ]. Due to the emerging role of PBL in RC complications, surgeons should be encouraged to cooperate closely with the anaesthesiologic unit and cautiously perform the surgeries, if possible, using available new technologies and haemostatic agents to decrease the rates of needless PBT.…”
Section: Resultsmentioning
confidence: 99%